The Effects of Intravenous Lipid Emulsion Therapy in the Prevention of Depressive Effects of Propofol on Cardiovascular and Respiratory Systems: An Experimental Animal Study - ONUR, ÖZGE ECMEL (MDPI, 2018)
Background and objectives: Although there are several hypotheses about the mechanism of action, intravenous lipid emulsion (ILE) therapy has been shown to be effective in the treatment of toxicities due to local anaesthetics and many lipophilic drugs. In this study, we had hypothesized that ILE therapy might also be effective in preventing mortality and cardiorespiratory depressant effects due to propofol intoxication. Materials and methods: Twenty-eight Sprague-Dawley adult rats were randomly divided into four groups. Saline was administered to the subjects in the control group. The second group was administered propofol (PP group); the third group was administered ILE (ILE group), and the fourth group was administered propofol and ILE therapy together (ILE+PP group). Systolic blood pressure (SBP), diastolic blood pressure (DBP), respiratory rate (RR), heart rate (HR), and mortality were recorded at 10 time-points during a period of 60 min. A repeated measures linear mixed-effect model with unstructured covariance was used to compare the groups. Results: In the PP group; SBP, DBP, RR, and HR levels declined steadily; and all rats in this group died after the 60-min period. In the ILE+PP group, the initially reduced SBP, DBP, RR, and HR scores increased close to the levels observed in the control group. The SBP, DBP, RR, and HR values in the PP group were significantly lower compared to the other groups (p < 0.01). The mortality rate was 100% (with survival duration of 60 min) for the PP group; however, it was 0% for the remaining three groups. Conclusions: Our results suggest that the untoward effects of propofol including hypotension, bradycardia, and respiratory depression might be prevented with ILE therapy.
Keywords: acute toxicity; cardiovascular depression; intravenous lipid emulsion; propofol; rat model; respiratory depression; INTRALIPID EMULSION; FATTY-ACIDS; RAT MODEL; BUPIVACAINE; INFUSION; PHARMACOKINETICS; RESUSCITATION; ELEVATION; PRESSURE